Sexuality, gender and HIV risk perception among Mexican indigenous women - Juárez-Moreno, Mariana; López-Pérez, Oresta; Raesfeld, Lydia Josefa; Durán-González, Rosa Elena (Saúde e Sociedade, 2021)
This research aims to understand the sexuality and gender practices of indigenous women, their knowledge and perception about HIV infection risk. For this purpose, an exploratory descriptive research was carried out, with a qualitative method, in which a semi-structured interview was applied to indigenous women from rural communities in Mexico. The results show that gender stereotypes mark substantial differences between men and women. Technological changes and migration have led to changes in access to information and family dynamics. Women are provided with more information on sexual and reproductive health in the public sphere, but this is not reflected in the private sphere, where it is difficult for them to discuss these issues with their family members, mainly their partner, which limits their control over their sexual and reproductive health. There is a lack of knowledge about HIV and others STI. Most women do not perceive themselves to be at risk of infection, and, at the community level, people with HIV are segregated. It is necessary to design, in collaboration with them, interventions with an intercultural approach and a gender perspective.